COMMUNICATION CHANNEL - Zeinolla, Nursat; Temirbayev, Ilyas; Sarsenbayeva, Aruzhan; Aisin, Arsen; Nurlanbek, Kainar (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This project sought to create a university communication platform designed to alleviate fundamental problems students encounter while trying to reach faculty or administrative departments like vague procedures, elongated response times, and concealment of information.
Keywords: Communication channel; type of access: open access